Foreign Languages’ Influence on Albanian Police Lexicon - Haziri, Shemsi (East European Journal of Psycholinguistics, 2020)
In this study we attempted to thoroughly explain influences of foreign languages on police lexicon in Albanian language, with special focus on the influence of Serbian and English language in Kosovo, as well as the influence of Italian and English language in Albania. Influence of Serbian language only on police lexicon in Kosovo has been created due to historic circumstances of development of police activities under specific conditions. The impact of Serbian language on police lexicon in Albanian language in Kosovo was prevailing for a long period, during which Kosovo was under Serbian rule. This linguistic influence at its highest level in time period between 1970-1990, when Albanian language was used in police activities in Kosovo. In that time period most of the police officers were of the Albanian ethnicity and Kosovo had the status of autonomous province (1974-1990). English influence on police lexicon in Kosovo started in 1999 after liberation of Kosovo. From 1999 to 2008, English was used as the official language together with local languages Albanian and Serbian. This influence has not been limited only to police activities but it has spread widely into all fields of activities in Albanian language in Kosovo. Influence of English language in police lexicon is also evident in Albania, with words like: brifing (alb) – briefing (en), lidership (alb) – leadership (en), staf (alb.)– staff (en), task force (alb) – task force (en), etc. On the other hand Italian language is an influential language in police lexicon only in Albania due to historical, economic and cultural development. As a result, this is manifested by some basic words denoting police activities in Albania derived from Italian, like: komisiariati (alb) – commissariato (it), kavaleri (alb) – cavaleria (it), Policia e Shtetit (alb) - Polizia di Stato (it).